2003
DOI: 10.1051/apido:2003024
|View full text |Cite
|
Sign up to set email alerts
|

Dietary dopamine causes ovary activation in queenless Apis mellifera workers

Abstract: -Groups of young honey bee workers were fed a diet containing dopamine while confined in small cages at 34°C and 80% RH in absence of a queen for 8 to 13 days. The bees in eight pairs of cages, each pair containing an equal number of workers, received a pollen-rich diet supplemented with dopamine (10 µg/g of diet) (DOP groups), or not supplemented (controls). The rate of consumption of the diet was monitored continuously during the confinement period, after which the workers were dissected to assess follicle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 39 publications
1
36
0
2
Order By: Relevance
“…Beggs et al (2007) showed that HVA reduces dopamine levels in the honeybee's brain. Because feeding of dopamine to worker bees elevates rates of ovarian activation (Dombroski et al 2003), HVA might be a potential agent within QMP involved in regulating worker sterility. Alas, HVA alone has not been demonstrated to cause suppression of worker ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Beggs et al (2007) showed that HVA reduces dopamine levels in the honeybee's brain. Because feeding of dopamine to worker bees elevates rates of ovarian activation (Dombroski et al 2003), HVA might be a potential agent within QMP involved in regulating worker sterility. Alas, HVA alone has not been demonstrated to cause suppression of worker ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence also suggests that dopamine is involved in the ovary development and egg-laying behaviors in honeybees (Brandes et al, 1990;Harris and Woodring, 1995;Nagao, 2001, 2002;Dombroski et al, 2003;Harano et al, 2005) as well as in other insects (Neckameyer, 1996;Boulay et al, 2001;Sasaki et al, 2007). However, the effects of dopamine on workers and queens seem contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this is a scarcity of empirical studies that show actual physiological effects of amines on fecundity and aggressiveness. Examples are limited to a few studies: oral administration of dopamine stimulates reproduction in honeybee queenless workers (Dombroski et al, 2003) and paper wasp workers (Sasaki et al, 2009). Another difficulty comes from the pleiotropic functions of biogenic amines.…”
Section: Introductionmentioning
confidence: 99%